Efektivitas Pengelolaan Dana Desa dalam Menunjang Pembangunan dan Pemberdayaan Masyarakat (Studi Desa Bontomanai Kecamatan Bungaya Kabupaten Gowa) - Muhammad Fachrul Syarlis; Siti Zakiah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
The purpose of this study is to provide an overview of Permendagri No. 13/2014 in supporting the development and empowerment of village communities starting from planning, implementation, administration, reporting, and accountability of village finances in Bontomanai Village in 2017-2018. The results showed that the planning stage was still oriented to physical development. The implementation phase is carried out by the activity management (TPK) but the realization of village development and community empowerment has not been carried out optimally. The administration phase has used the Village Financial System Application (SISKEUDES). In the reporting phase, Bontomanai village head has reported the realization of the use of the budget to the Regent of Gowa. In the accountability stage, the head of Bontomanai village has socialized the use of the village budget to the local government (Bupati), Dewan Musyawarah Desa, and community leaders.